An Emic Perspective and Ethnoscience Methods for Organizational Research - Morey, Nancy C.; Luthans, Fred (Academy of Management Review, 1984)
This paper is in answer to the call for new, innovative perspectives and methodologies for organizational research. Although the approach here falls within the subjective/idiographic/qualitative/insider set of methodologies rather than the objective/nomothetic/quantitative/outsider set, there is the potential to bridge the gap between the two sets. Coming largely from anthropology, the emic perspective is explained; the specific steps for ethno-science analyses are summarized; and examples and implications are given.